EVALUASI PENYELENGGARAAN PENGARUSUT AMAAN GENDER (PUG) KOTA SEMARANG - Indra Kertati (Jurnal Riptek, 2019)
Gender mainstreaming (PUG) is a strategy of integrating gender issues in the budget planning process. The aim is to ensure that gender issues can be resolved properly by the government. The mandate for organizing the PUG is contained in Presidential Instruction number 9 of 2000 concerning Gender Mainstreaming of the National Development Plan. Although this mandate has been formulated since 2000, the Government of Indonesia has actually signed various conventions for gender equality, protection and justice. These mandates were then narrowed down in 7 prerequisites for Gender Mainstreaming, namely commitment, policy, institutional, gender and child data systems, tools, human resources, and community participation. Prerequisites Gender Mainstreaming is one order in achieving gender equality and justice. The Semarang City Government is struggling to meet the prerequisites for achieving gender equality and justice, but the evaluation results showed that there are some components that cannot be fulfilled. Evaluation theory that compares indicators and performance achievements has shown several prerequisites that are not achieved optimally such as commitment, human resources, and tools. This descriptive qualitative study specifically recommends that the City of Semarang immediately accelerate commitments in the form of drafting Regional Regulations on Gender Mainstreaming, as well as gender responsive planning policies that are integrated in the regular process.